First record of the parasitic barnacle Anelasma squalicola Darwin, 1852 (Pollicipedomorpha: Pollicipedidae) in the Eastern Pacific Ocean and a new host report: Etmopterus benchleyi Vásquez, Ebert & Long, 2015 (Squaliformes: Etmopteridae) - Angulo, Arturo; Sibaja-Cordero, Jeffrey A. (Zootaxa, 2021)
Anelasma squalicola is a parasitic barnacle of members of the deep-water shark families Etmopteridae, Pentanchidae and Scyliorhinidae. We report the first published confirmation of this species in the Eastern Pacific Ocean, based on material collected off Costa Rica, its first record as a parasite of the Ninja lantern shark, Etmopterus benchley (Etmopteridae), and a new size record for the host. The information presented herein expands the knowledge (distribution and host usage) of this enigmatic species.